2018
DOI: 10.1016/j.hrthm.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Reduced left ventricular mechanical dispersion at 6 months follow-up after cardiac resynchronization therapy is associated with superior long-term outcome

Abstract: Larger LVMD at 6 months after CRT is independently associated with all-cause mortality and VA. LVMD may be valuable in identifying patients who remain at high mortality risk after CRT implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…The standard deviation of these 17 segments, so-called mechanical dispersion, represents the heterogeneity of electrical conduction in the myocardium (figure 4c). Increased LV mechanical dispersion has been associated with increased risk of SCD and/or ventricular arrhythmias in patients after STEMI, heart failure patients receiving cardiac resynchronisation therapy but also in hypertrophic cardiomyopathy patients where mechanical dispersion was also associated with myocardial fibrosis [72,74,77]. The Rotterdam study, a population-based cohort study among 14 926 participants, demonstrated a >30% increased risk of SCD in patients with COPD, especially in those with frequent exacerbations [78].…”
Section: Size and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The standard deviation of these 17 segments, so-called mechanical dispersion, represents the heterogeneity of electrical conduction in the myocardium (figure 4c). Increased LV mechanical dispersion has been associated with increased risk of SCD and/or ventricular arrhythmias in patients after STEMI, heart failure patients receiving cardiac resynchronisation therapy but also in hypertrophic cardiomyopathy patients where mechanical dispersion was also associated with myocardial fibrosis [72,74,77]. The Rotterdam study, a population-based cohort study among 14 926 participants, demonstrated a >30% increased risk of SCD in patients with COPD, especially in those with frequent exacerbations [78].…”
Section: Size and Functionmentioning
confidence: 99%
“…Novel imaging techniques could further help to identify patients at risk for adverse events during follow-up. Insert images taken from figure 4 and reproduced with permission as previously stated [70][71][72][73] with permission from the publisher.…”
Section: Figurementioning
confidence: 99%
“…Of these 11 studies, 9 studies met the predefined inclusion criteria for the systematic review, including 3,981 patients with symptomatic heart failure, undergoing CRT implantation, with complete results for GLS and the primary inclusion endpoint (see Fig. 1 ) [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] . The remaining 2 studies were excluded due to no clear data on the prespecified primary combined outcome.…”
Section: Resultsmentioning
confidence: 99%
“…There was variation between the design of included studies, with 2 being randomised controlled trials [15] , [18] , 3 prospective cohort studies [14] , [16] , [19] and 4 retrospective cohort studies [13] , [17] , [20] , [21] of which 2 studies shared similar patient populations from the same site [13] , [21] . Table 1 provides a complete description of the included study designs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation